"Sometimes it's harder to see than to experience": The sibling subsystem in the context of parental abuse as conveyed by adult survivors. (July 2022) - Katz, Carmit; Hindi, Inbal; Kanar, Shikma; Tener, Dafna
Highlights: 20 adults survivors discussed the central role of the sibling subsystem in the context of parental abuse. Survivors described the sibling subsystem as providing them with comfort and support. The sibling subsystem was perceived as one that was essential to their emotional and physical survival. In adulthood, survivors shared two relationship profiles: closeness and distance. Distance was perceived as a way to contend with the trauma. Abstract: Parental abuse is a common social problem that can have far-reaching consequences for all those involved, including the sibling subsystem. The current study was designed to examine the way the sibling subsystem is experienced and perceived by adult survivors of parental abuse. The study sample comprised 20 adults from different families who experienced parental abuse as children and had at least one sibling. The survivors discussed the central role of the sibling subsystem in their childhood. They described the sibling subsystem as providing them with comfort and support and that it was essential to their emotional and physical survival of the parental abuse. Additionally, the survivors shared two relationship profiles in adulthood: closeness and distance. Although distinct in nature, these two profiles were described by the survivors as their way of contending with the painful memories of their childhood. The discussion addresses the contribution of the current study to the understanding of the sibling subsystem dynamic in both childhood and adulthood. It also stresses the need to put the sibling subsystem at the center of theoretical and empirical discussions as well as a focus on therapeutic interventions and prevention to promote the wellbeing of children and adult survivors of parental abuse.